The XVI International Organisation of Science and Technology Education (IOSTE) Symposium Borneo 2014 - Chan, Margaret (UiTM Sarawak, 2015)
The International Organisation of Science and Technology Education (IOSTE) was established in 1979 to promote contact and dialogue across political and ideological borders with the key concern that education in Science and Technology should be a vital part of the general education of the peoples of all countries. Its mission statement is that IOSTE identifies science and technology education with the real and changing needs of humankind as a whole and with specific needs of its component communities and nations. It has memberships from 1 5 regions and eighty countries that include South West Pacific, South East Asia, Far East Asia, South Asia, Persian Gulf, West Africa, East and Central Africa, Southern Africa, Mediterranean, Eastern and Central Europe, Nordic Countries, West Europe, South America, North America and Central America.